Solid‐State Structure of Tris‐Cyclopentadienide Uranium(III) and Plutonium(III). Issue 12 (27th December 2017) - Apostolidis, Christos; Dutkiewicz, Michał S.; Kovács, Attila; Walter, Olaf
Abstract: The organometallic tris‐cyclopentadienide actinide(III) (AnCp3 ) complexes were first reported about 50 years ago. However, up until now, only the NpCp3 solid state structure has been studied. Here we report on the solid state structures of UCp3 and PuCp3 which are isostructural to the Np analogue. The structural models are supported by theoretical calculations and compared to their lanthanide analogues. The observed trends in changes of bond lengths might be indicator for an increased covalency in the bonding in the tris‐cyclopentadienide actinide(III) complexes (AnCp3 ) compared to their lanthanide homologues. Abstract : New questions from the end of an old story : By presenting the solid‐state structure of UCp3 and PuCp3 this final knowledge gap is closed now. The structural differences between actinides and lanthanides in their non‐stabilised complexes MCp3 could contribute to a better understanding of covalency in the actinide complexes.